The feasibility and efficacy of coach-led virtual home-based cycling among individuals with cerebral palsy - Larsen, Lisbeth Hoejkjaer; Kirk, Henrik; Lorentzen, Jakob (Frontiers in Neurology, 2025)
IntroductionCerebral palsy (CP) is a neurological disorder that impairs motor control and coordination, often leading to physical and social restrictions in daily activities. This single-arm feasibility study investigates the potential efficacy of virtual moderate- to high-intensity cycling at home among individuals with CP.MethodsTwenty-three individuals with CP (GMFCS I-IV; 16 males; mean age 26, range 13–58 years) were recruited for a 12-week home-based cycling intervention. The intervention included three weekly sessions, which could be completed either in an online coach-led group setting or independently, along with guidance for additional training. The primary focus was feasibility, addressed by retention, adherence, and safety. Efficacy was primarily evaluated using a functional threshold power test for cycling (FTP), the Timed Up and Go Test (TUG), and the Sit to Stand test (STS), assessed before and after the intervention, and secondly via self-reported questionnaires.ResultsThe intervention was demonstrated to be safe and feasible, with no adverse events reported. Retention was high, with only one dropout attributed to mononucleosis. The remaining 22 participants completed the study with a high attendance averaging 3.1 sessions/week [range 2–5]. Improvements were observed in the FTP test (67.2 ± 37.3 W, p < 0.001), the TUG test (2.1 ± 1.4 s, p < 0.001), and the STS test (3.9 ± 3.3 repetitions, p < 0.001) while self-reported fatigue, pain, sleep, well-being, and self-efficacy remained unchanged.DiscussionOur findings suggest that virtual cycling at home is a safe and feasible approach to engage in moderate- to high-intensity exercise, enhance physical capacity, and improve functional activity outcomes for individuals with activity limitations.